The Functional and Antiviral Activity of Interferon Alpha-Inducible IFI6 Against Hepatitis B Virus Replication and Gene Expression - Sajid, Muhammad; Ullah, Hafiz; Yan, Kun; He, Miao; Feng, Jiangpeng; Shereen, Muhammad Adnan; Hao, Ruidong; Li, Qiaohong; Guo, Deyin; Chen, Yu; Zhou, Li (Frontiers in Immunology, 2021)
Hepatitis B virus is an enveloped DNA virus, which infects more than three hundred and sixty million people throughout the world and leads to severe chronic liver diseases. Interferon-alpha inducible protein 6 (IFI6) is an interferon-stimulated gene (ISG) whose expression is highly regulated by the stimulation of type I interferon-alpha that restricts various kinds of virus infections by targeting different stages of the viral life cycle. This study aims to investigate the antiviral activity of IFI6 against HBV replication and gene expression. The IFI6 was highly induced by the stimulation of IFN-α in hepatoma cells. The overexpression of IFI6 inhibited while knockdown of IFI6 elevated replication and gene expression of HBV in HepG2 cells. Further study determined that IFI6 inhibited HBV replication by reducing EnhII/Cp of the HBV without affecting liver enriched transcription factors that have significant importance in the regulation of HBV enhancer activity. Furthermore, deletion mutation of EnhII/Cp and CHIP analysis revealed 100 bps (1715-1815 nt) putative sites involved in IFI6 mediated inhibition of HBV. Detailed analysis with EMSA demonstrated that 1715-1770 nt of EnhII/Cp was specifically involved in binding with IFI6 and restricts EnhII/Cp promoter activity. In vivo analysis based on the hydrodynamic injection of IFI6 expression plasmid along with HBV revealed significant inhibition of HBV DNA replication and gene expression. Overall, our results suggested a novel mechanism of IFI6 mediated HBV regulation that could lead to developing potential therapeutics for efficient HBV infection treatment.